2021
DOI: 10.3390/curroncol28060418
|View full text |Cite
|
Sign up to set email alerts
|

Association between Ureteral Clamping Time and Acute Kidney Injury during Robot-Assisted Radical Cystectomy

Abstract: Robot-assisted radical cystectomy (RARC) is replacing open radical cystectomy (ORC) and requires clamping of the ureters, resulting in a predisposition to postrenal acute kidney injury (AKI). We investigated the association between ureteral clamping or its duration and acute/chronic postoperative kidney function. Patients who underwent radical cystectomy (robotic or open) at two tertiary institutions during 2002–2021 were retrospectively enrolled. In those who underwent RARC, the maximum postoperative percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Their ndings showed that early postoperative AKI occurred in 100 out of 912 patients (11%). The high incidence of AKI is thought to be due to prolonged surgical clamping of the ureter, which hinders urine drainage [32] . In the patients who underwent MLRC, ureters were not clamped immediately after the ureters were completely dissociated.…”
Section: Discussionmentioning
confidence: 99%
“…Their ndings showed that early postoperative AKI occurred in 100 out of 912 patients (11%). The high incidence of AKI is thought to be due to prolonged surgical clamping of the ureter, which hinders urine drainage [32] . In the patients who underwent MLRC, ureters were not clamped immediately after the ureters were completely dissociated.…”
Section: Discussionmentioning
confidence: 99%
“…8 A retrospective study identified prolonged clamping of the ureters during robot-assisted radical cystectomy as a causative factor for acute kidney injury (AKI). 9 AKI may result in metabolic acidosis, hyperkalemia, and cardiovascular complications. 10 Additionally, pneumoperitoneum during robot-assisted radical cystectomy adversely affects renal function through its negative effects on renal blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to avoiding unnecessary manipulation of the ureters and minimizing operation length, minimization of ureteral clamping may contribute to better renal function preservation. 4 In contrast, the introduction of an enhanced recovery after surgery protocol, now widely utilized, may require extra caution to reduce the risk of AKI. 5 However, more data on intra-and pre/post-operative risk factors for renal function loss are needed, and such investigations are highly warranted.…”
mentioning
confidence: 99%
“…Surgery itself also requires continuous refinement. In addition to avoiding unnecessary manipulation of the ureters and minimizing operation length, minimization of ureteral clamping may contribute to better renal function preservation 4 . In contrast, the introduction of an enhanced recovery after surgery protocol, now widely utilized, may require extra caution to reduce the risk of AKI 5 .…”
mentioning
confidence: 99%